Expanded CUG Repeats Trigger Disease Phenotype and Expression Changes through the RNAi Machinery in C. elegans. Issue 9 (19th April 2019) - Qawasmi, Lena; Braun, Maya; Guberman, Irene; Cohen, Emiliano; Naddaf, Lamis; Mellul, Anna; Matilainen, Olli; Roitenberg, Noa; Share, Danielle; Stupp, Doron; Chahine, Haya; Cohen, Ehud; et al.
Abstract: Myotonic dystrophy type 1 is an autosomal-dominant inherited disorder caused by the expansion of CTG repeats in the 3′ untranslated region of the DMPK gene. The RNAs bearing these expanded repeats have a range of toxic effects. Here we provide evidence from a Caenorhabditis elegans myotonic dystrophy type 1 model that the RNA interference (RNAi) machinery plays a key role in causing RNA toxicity and disease phenotypes. We show that the expanded repeats systematically affect a range of endogenous genes bearing short non-pathogenic repeats and that this mechanism is dependent on the small RNA pathway. Conversely, by perturbating the RNA interference machinery, we reversed the RNA toxicity effect and reduced the disease pathogenesis. Our results unveil a role for RNA repeats as templates (based on sequence homology) for moderate but constant gene silencing. Such a silencing effect affects the cell steady state over time, with diverse impacts depending on tissue, developmental stage, and the type of repeat. Importantly, such a mechanism may be common among repeats and similar in human cells with different expanded repeat diseases. Graphical Abstract: Model of RNA pathogenic mechanism in DM1. The RNA interference machinery is activated by aberrant repeats and augments global translation. When repeat transcripts are generated, they are targeted by RNAi machinery proteins (Dicer and Argonaute). Dicer cleaves the repeats into small, RNA fragments that are used by the Argounate proteins as templates to find and silence other mRNAs with complementary sequences. Since many genes in the genome have repeated sequences, we found that the RNAi machinery is capable of destroying the RNA of unrelated genes. Over time, this can result in an unspecific reduction of gene expression and affect protein function and steady state. Unlabelled Image Highlights: We further developed our C. elegans model that recapitulates many human myotonic dystrophy symptoms, including muscular dysfunction and impaired stress response. We demonstrated genetically that the expression of an expanded repeat systematically causes downregulation in a range of endogenous genes bearing short non-pathogenic repeats and that this mechanism is dependent on the small RNA pathway. We established that RNA interference plays a key role in causing RNA toxicity in a C. elegans myotonic dystrophy type 1 model and that silencing of the RNAi pathway leads to a rescue of disease phenotypes.